Aktionsverben im inter- und intralingualen Vergleich:: Die IMAGACT-Ontologie und ihre Erweiterung um Deutsch - Gärtig-Bressan, Anne-Kathrin (Linguistik Online, 2019)
This paper examines transparent and non-transparent diminutive forms in Akan and the range of meanings associated with each group, as presented in Appah/Amfo (2011). It takes the discussion of Akan diminutives a step further by showing that some of the meanings communicated by transparent diminutive forms are dependent on the context, including the semantic properties of the base to which the diminutive morpheme is attached. In addition, it demonstrates that even though the non-transparent diminutive forms communicate diminu-tive meanings and contain what appears to be the Akan diminutive morpheme, synchronical-ly they are formally unanalyzable since the putative diminutive morpheme cannot be deline-ated from the base. Also, it is argued that these forms have come from a lexicalization pro-cess that resulted in the reanalysis of the base+diminutive morpheme as a single unanalyza-ble unit. It is observed that the process of lexicalization could have been facilitated by a number of factors, including the loss of the bases from the language, which meant that the putative base could only be found in the context of their diminutive use. Finally, the lexical-ization process is schematized using formalism from Construction Morphology.